New tool to investigate toxicological hazard due to endocrine disruptors in mediterranenan cetaceans - Fossi, M. C.; Marsili, L. (2006)
Mediterranean cetaceans, particularly odontocetes, accumulate high concentrations of organochlorine contaminants (OCs) and are therefore exposed to high toxicological risk. Some OCs are known to be endocrine disrupting compounds (EDCs). The hypothesis that Mediterranean cetaceans (Stenella coeruleoalba, Delphinus delphis, Tursiops truncatus and Balaenoptera physalus) are subject to toxicological risk due to organochlorines and emerging contaminants, such as polybrominated diphenyl ethers (PBDEs) with endocrine disrupting capacity, was investigated using non-lethal “diagnostic” and “prognostic” methods. CYP1A1 activity induction (Benzo(a)pyrene monooxygenase) in skin biopsies was used as a “diagnostic” indicator of exposure to organochlorines in odontocetes and mysticetes and in different populations of Stenella coeruleoalba. Marked differences in levels of OCs and CYP1A1 activity were found between fin whales and odontocetes. Organochlorine levels and CYP1A1 activity were significantly higher in the Stenella coeruleoalba population of the Mediterranean Whale Sanctuary than in those of two other study areas, suggesting that cetaceans are exposed to high risk in this protected area. Several questions remain still unanswered in ecotoxicological studies of Mediterranean cetaceans. The need for new biomarkers for EDCs and for a “cell model” to explore the different susceptibilities to several classes of ECDs, including emerging contaminants, led us to culture fibroblasts of different cetacean species as a non-lethal new investigation tool (“dolphins in test tubes”). As a new “prognostic” tool we explored interspecies and gender susceptibility to OC-EDCs and PBDEs using qualitative and semi-quantitative evaluation of target proteins, such as CYP1A1 and CYP 2B in cultured cetacean (Stenella coeruleoalba, Tursiops truncatus and Balaenoptera physalus) fibroblasts, by western blot, immunofluorescence technique and PCR real time. The information obtained in this pilot experiment will be the basis for further applications ...